Política fiscal e informalidade: análise de choques de produtividade por meio de um modelo DSGE para o Brasil - Felix, João Anderson da Silva (2019)
The purpose of this paper is to develop a stochastic dynamic general equilibrium model.(DSGE) that takes into account an economy with an informal sector. The importance of including the informal economy in a DSGE model is due to the macroeconomic distortions that this sector causes. For the analysis that the informal sector causes in the Brazilian macroeconomic variables, it was used as reference work the article Fiscal policy with fiscal policy with an informal sector by Dellas Harris e Malliaropoulos (2017) The results have shown that shocks of formal productivities have positive effects on the formal and informal sectors. On the other hand, the growth of the informal sector negatively affects the formal sector of the economy. Also is found that the laffer curves constructed from the developed model show that the tax rate that maximizes the country’s revenues is around 55 %, there were built three scenarios where informality can be taxed or not.